2016
DOI: 10.1242/dev.127944
|View full text |Cite
|
Sign up to set email alerts
|

Mammary epithelial tubes elongate through MAPK-dependent coordination of cell migration

Abstract: Mammary branching morphogenesis is regulated by receptor tyrosine kinases (RTKs). We sought to determine how these RTK signals alter proliferation and migration to accomplish tube elongation in mouse. Both behaviors occur but it has been difficult to determine their relative contribution to elongation in vivo, as mammary adipocytes scatter light and limit the depth of optical imaging. Accordingly, we utilized 3D culture to study elongation in an experimentally accessible setting. We first used antibodies to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 68 publications
(75 reference statements)
4
59
0
Order By: Relevance
“…Increased Ret signaling at the tips of kidney tubules promotes cell migration (Riccio et al, 2016), and FGF receptor activation at the tips of mammary terminal end buds signals to stimulate tip cell migration (Huebner et al, 2016). Based on the results presented here, we now propose that Btbd7 is a crucial regulator of differential cell migration in the outer bud cells of developing salivary glands.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Increased Ret signaling at the tips of kidney tubules promotes cell migration (Riccio et al, 2016), and FGF receptor activation at the tips of mammary terminal end buds signals to stimulate tip cell migration (Huebner et al, 2016). Based on the results presented here, we now propose that Btbd7 is a crucial regulator of differential cell migration in the outer bud cells of developing salivary glands.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, mammalian epithelial branching organs undergo collective migration in the absence of these invasive leading-edge membrane protrusions (Ewald et al, 2008;Schnatwinkel and Niswander, 2013). Live imaging of the salivary gland (Hsu et al, 2013;Larsen et al, 2006), lung (Schnatwinkel and Niswander, 2013), kidney (Riccio et al, 2016), mammary gland (Huebner et al, 2016) and pancreas (Shih et al, 2016) have all revealed that the peripheral bud tip cells in these organs are more dynamic compared with inner bud and ductal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first, we seek to understand how mammary epithelial tubes elongate, bifurcate, and polarize during normal development. We have defined the basic cell movements during each process and identified key regulators of each step (1). We are now collaborating with engineers to integrate our experimental understanding into predictive models.…”
Section: What Are You Currently Working On? What Is Up Next For You?mentioning
confidence: 99%
“…The second area focuses on using 3D culture and animal models to understand how the tumor microenvironment cooperates with genetic changes to affect cell behavior within intact tissues. We have demonstrated that the extracellular matrix is a potent regulator of cancer invasion (2), that activation of individual signaling nodes can drive complex tissue level behaviors (1), and that mammary cells can be induced to disseminate without losing their epithelial character (3). We are now extending these efforts by working with systems biologists to understand how information flows from DNA to protein to signaling as cells reprogram from normal to malignant phenotypes, and with oncologists to identify targets for anti-metastatic therapy.…”
Section: What Are You Currently Working On? What Is Up Next For You?mentioning
confidence: 99%